PERAN DUKUNGAN SOSIAL ORANGTUA, TEMAN SEBAYA, DAN GURU TERHADAP SCHOOL WELL-BEING SISWA PESANTREN X - Irena Nova Wijaya; Riana Sahrani; Fransisca Iriani R. Dewi (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2020)
Islamic boarding schools’ education has its own challenges, higher academic loads, longer duration, and other rules that need to be followed. Students' experiences in school will shape students' judgment of their school. Students’ judgment toward their school is defined as school well-being. Researches said that social support has roles in several school well-being dimensions. But there is no research linking social support with a whole school well-being’s dimension. In addition, studies on social support variables (parents, teachers, and peers) and school well-being in the context of Islamic boarding schools are still limited. This study examines the role of parents’, peer groups’, and teachers’ social support in X Islamic Boarding School regarding student’s School Well-Being. This quantitative research, with purposive sampling technique, include 115 teenagers who live in X boarding school. X Islamic boarding school is a modern Islamic boarding school, accredited with C grade, and most of the students come from disadvantaged families. Subject’s average age is 17 years old with (33.9%) boys and (66.1%) girls. Data analysis was done with correlation and regression descriptive statistics. The main result of the research shows that parent’s, peer groups’, and teacher’s social support have no role in X boarding school student’s school well-being (F=0,785, p=0,505>0,05). Further researches data shows parent’s support, peer groups’ support, teacher’s support and school well-being in X Islamic boarding school classified as quiet high. Although, dimension having and being, classified as quiet low. Furthermore, there are parents’, peer groups’ and teachers’ social support role in school well-being’s loving dimension. Pendidikan pesantren memiliki tantangan tersendiri, seperti beban akademis yang lebih tinggi, waktu yang lebih panjang, dan berbagai peraturan yang harus dijalankan. Pengalaman siswa di sekolah akan membentuk penilaian siswa terhadap sekolahnya. Penilaian siswa akan sekolahnya disebut school well-being. Beberapa penelitian menunjukkan dukungan sosial memiliki peran dalam beberapa dimensi dalam school well-being. Namun belum ada penelitian yang menghubungkan dukungan sosial dengan school well-being secara menyeluruh. Selain itu kajian mengenai varibel dukungan sosial (orangtua, guru, dan teman sebaya) dan school well-being dalam konteks pesantren atau sekolah asrama masih terbatas. Penelitian ini bertujuan menguji peran dukungan sosial orangtua, teman sebaya, dan guru terhadap school well-being di pesantren X. Sebanyak 115 remaja menjadi sampel diambil dengan purposive sampling yang berasal dari pesantren X. Pesantren X adalah pesantren modern, terakreditasi C, dan sebagian besar siswa adalah kaum dhuafa. Rerata subyek adalah 17 tahun dengan jenis kelamin laki-laki (33,9%) dan perempuan (66,1%). Analisis data dilakukan dengan statistik deskriptif, uji korelasi, dan regresi. Hasil utama penelitian menunjukkan tidak terdapat peran dukungan sosial orangtua, teman sebaya, dan guru terhadap school well-being pada siswa pesantren X (F=0,785, p=0,505>0,05). Hasil penelitian tambahan menunjukkan gambaran dukungan orangtua, dukungan teman sebaya, dukungan guru, dan school well-being pesantren X tergolong cukup tinggi. Namun pada gambaran dimensi having dan being torgolong cukup rendah. Selanjutnya, terdapat peran dukungan sosial orangtua, dukungan sosial teman, dan dukungan sosial guru terhadap dimensi loving pada variabel school well-being.